Research progress of transient absorption spectroscopy in solar energy conversion and utilization - Zhang, Fengying; Mei, Yanglin; Jiang, Yuman; Zheng, Shenshen; Zheng, Kaibo; Zhou, Ying (Wuli Huaxue Xuebao/ Acta Physico - Chimica Sinica, 2025)
With the development of ultrafast laser technology, time-resolved spectroscopy has become an essential tool to study the microscopic photophysical mechanisms on ultrafast time scales in the field of solar energy conversion and utilization. Transient absorption spectroscopy (TAS), as an essential technology for studying photoinduced ultrafast electron transfer and photo-induced carrier dynamics, has the unique advantage of revealing key dynamic processes, such as the generation, separation, transport, and recombination of photogenerated carriers. Focusing on light-to-chemical and light-to-electrical energy conversion, this review summarizes TAS applications in two primary solar energy conversion systems: photocatalysis and solar cells. Firstly, according to the different requirements of photocatalysis (emphasizing migration for surface reactions) and solar cells (highlighting interfacial carrier separation efficiency), we summarize design strategies and recent advances for enhancing carrier utilization from three perspectives: electron manipulation, hole manipulation and surface interfacial processes. Subsequently, special attention is given to how in situ spectroscopy elucidates the influence mechanisms of microscopic energy conversion processes and device performance under complex application scenarios involving photo-electro-thermal couplings. Finally, the forward-looking development direction of basic research in solar energy conversion and utilization is summarized, which provides theoretical support for rational design and performance optimization of solar energy conversion materials, reactions, and devices.
Keywords: In situ spectroscopy; Photocatalysis; Solar cells; Solar energy conversion and utilization; Transient absorption spectroscopy